2017
DOI: 10.15403/jgld.2014.1121.264.hcv
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Occurrence and Recurrence after Antiviral Treatment in HCV-Related Cirrhosis. Are Outcomes Different after Direct Antiviral Agents? A Review

Abstract: Hepatitis C virus (HCV) infection is one of the major causes of hepatocellular carcinoma (HCC) worldwide. In the last decades, several studies have showed a lower rate of HCC occurrence or recurrence in patients with HCV-related cirrhosis after interferon-based antiviral therapies compared to untreated controls, even without reaching viral clearance. Unfortunately, interferon regimens could only yield viral clearance in approximately half of the patients. The recent development of new all-oral regimens with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 47 publications
0
12
0
7
Order By: Relevance
“…Other reports regarding this issue could not find clear relationship. Spârchez et al [23] in a review article regarding this issue concluded that the current available literature is unclear and the risk of HCC needs to be better clarified with prospective randomized controlled trials. Kanwal et al [24] found that the overall annual incidence of HCC was markedly higher in patients who did not achieve SVR with direct-acting antiviral drugs compared to those who did.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports regarding this issue could not find clear relationship. Spârchez et al [23] in a review article regarding this issue concluded that the current available literature is unclear and the risk of HCC needs to be better clarified with prospective randomized controlled trials. Kanwal et al [24] found that the overall annual incidence of HCC was markedly higher in patients who did not achieve SVR with direct-acting antiviral drugs compared to those who did.…”
Section: Discussionmentioning
confidence: 99%
“…Houve dessa forma, uma otimização farmacocinética que possibilitou concentrações séricas mais elevadas e mais duradouras que agiam com pressão constante sobre o vírus. Além disso, possibilitou a administração de apenas uma injeção semanalmente [34][35][36] .…”
Section: Tratamento Até 2011unclassified
“…After almost one decade of experience, there is now clear data that DAA therapy lowers HCC occurrence 3,11 . Moreover, after the initial alarming reports of a higher recurrence rate in patients with previous HCC treatment, 12 we now have prospective studies providing evidence that the risk of early HCC recurrence after DAA therapy is similar to or lower than what was observed in interferon‐treated or untreated controls, thus settling the initial concerns 13,14 .…”
Section: Introductionmentioning
confidence: 95%